Full transparency of politicians' actions does not increase the quality of political representation - David Stadelmann; Marco Portmann; Reiner Eichenberger (Center for Research in Economics, Management and the Arts (CREMA), 2013)
We identify the impact of transparency in political decision -making on the quality of political representation with a difference- in-difference strategy. The quality of political representation is measured by observed divergence of parliamentary decisions from revealed voter preferences on the very same issues. Full transparency of votes of individual politicians does not decrease divergence from voter preferences.
Keywords: D70; D80; H11; 330; Transparency; quality of political decisions; representation; parliament; individual votes; referenda